Prevention and management of CMV infection in pediatric solid organ transplant recipients - Balani, Shanthi S.; Sadiq, Sanober; Jensen, Chelsey J.; Kizilbash, Sarah J. (Frontiers in Pediatrics, 2023)
Human cytomegalovirus (CMV) remains one of the most common opportunistic infections following solid organ transplantation in children. CMV causes morbidity and mortality through direct tissue-invasive disease and indirect immunomodulatory effects. In recent years, several new agents have emerged for the prevention and treatment of CMV disease in solid organ transplant recipients. However, pediatric data remain scarce, and many of the treatments are extrapolated from the adult literature. Controversies exist about the type and duration of prophylactic therapies and the optimal dosing of antiviral agents. This review provides an up-to-date overview of treatment modalities used to prevent and treat CMV disease in solid organ transplant (SOT) recipients.